Moving Target Tracking for Single UAV In Open Outdoor Environment - Xiao, Zhenliang; Liu, Daqian; Fei, Bowen; Men, Tong; Zhou, Zhijian; Zhang, Xiongtao; Zhou, Yun (2020 6th International Conference on Big Data and Information Analytics (BigDIA), 2020)
The task of tracking a moving target by the UAV has two major challenges: one is that the multi-angle and multi-scale changes caused by the target motion make the target detection more difficult, and the other is the target loss due to variable direction of movement. Most of the existing research is limited to simulation studies, while the remaining few studies only allow the UAV to track specific target in specific environments. In order to solve these problems, we design and validate a new system framework for UAV tracking moving target in an open outdoor environment. In this framework, we use YOLOv3 to detect the multi-angle and multi-scale moving target, locate the target based on monocular vision, and design a tracking strategy, Mass Spring Algorithm (MSA), to prevent the loss of moving target. The experimental video 1 1 https://www.bilibili.com/video/BV1SD4y197gF/ shows that the system framework we designed is effective and successful. The results of comparative experiments to MSA shows that it effectively prevents the loss of target in the tracking process.